THE Analysis of the Comparison of Bank Financial Performance Before and After the Merger on Company Value (Case Study on Bank BSI and Bank Islam Malaysia Berhad) - Dea Arifatul Alia; Feri Dwi Riyanto (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study aims to analyze the comparison of the financial performance of Bank Syariah Indonesia (BSI) and Bank Islam Malaysia Berhad (BIMB) before and after the merger, using the financial variables Return on Asset (ROA), Return on Equity (ROE), Financing to Deposit Ratio (FDR), Operating Costs to Operating Income, Non-Performing Financing (NPF), and Earning Per Share (EPS). This research uses a quantitative-comparative approach with data analyzed through descriptive statistical tests, classical assumption tests, and hypothesis tests. The results showed that the merger had a significant impact on the financial performance of both banks, although the effect varied depending on each variable and country context. In general, the merger improved operational efficiency and competitiveness, especially for BSI, which showed significant operational efficiency and scale improvements. However, there were some variables for which the results were not significant for Bank Islam Malaysia Berhad, indicating the different internal and external factors that influenced the merger outcome.